Ar, CCl4 and C6H6 adsorption outside and inside of the bundles of multi-walled carbon nanotubes—simulation study - Furmaniak, S.; Terzyk, A.; Gauden, P.; Wesolowski, R.; Kowalczyk, Poitr (Royal Society of Chemistry, 2009)
This is the first paper reporting the results of systematic study of the adsorption of Ar, C6H6 andCCl4 on the bundles of closed and opened multi-walled carbon nanotubes. Using grand canonicalMonte Carlo (GCMC) and molecular dynamics (MD) simulations, we also study the effect of theintroducing defects in the external and internal walls of osculating and separated nanotubes onAr diffusion and on adsorption of all three adsorbates. The Ar diffusion coefficients obtained arevery sensitive to the presence of defects. Simulated isotherms are discussed to show the relationbetween the shapes of the high resolution as-plots and the mechanisms of adsorption. Fromobtained data, as well as from geometric considerations, from the VEGA ZZ package, and fromsimulations (ASA), the values of surface areas of all nanotubes are calculated and compared withthose obtained using the most popular adsorption methods (BET, as and the A,B,C-points). Weshow that the adsorption value for the C-point of the isotherm should be taken for thecalculation of the specific surface area of carbon nanotubes to obtain a value which approachesthe absolute geometric surface area. A fully packed monolayer is not created at the A-, B- orC-points of the isotherm; however, the number of molecules adsorbed at the latter point is closestto the number of molecules in the monolayer as calculated via the ASA method, the VEGA ZZpackage or from geometric considerations.